Tinjauan Atas Pengakuan, Pengukuran Dan Pelaporan Pendapatan Berdasarkan PSAK 72 Pada PT Eca Indonesia - Anggraini, Chika; SETIAWAN, HENDRA; Taqyudin, Yudin (Jurnal Aplikasi Bisnis Kesatuan, 2025)
Companies in the recognition, measurement, and reporting of revenue must be carried out under applicable financial standards so that revenue can be fairly reported on the presentation of the company's financial statements which will then be accountable to internal and external parties.  Financial standards relating to revenue are regulated in Statement of Financial Accounting Standards (PSAK) No. 72 concerning Revenue from Contracts with Customers. PSAK 72 is effective from January 1, 2020, and replaces the previous PSAK 23 on Revenue. The purpose of the preparation of this Final Project is to determine the process of recognition, measurement, and reporting of revenue earned in a company engaged in drilling and blasting services. Another objective is to ensure the suitability of the application of PSAK 72 in the recognition and measurement of revenue whether it has been implemented per applicable accounting standards. In general, the recognition, measurement, and reporting of revenue at PT ECA Indonesia have been carried out fairly. In the application of PSAK 72 at PT ECA Indonesia, there are several conformities. The conformity in question is found in PSAK 72 paragraphs 9, 22, 27, 31, 47, and 76.